Evaluating the Effectiveness of Compensation Systems on Employee Motivation and Retention in Auto Parts Enterprises in Wuhan, China: Basis For Human Resource Optimization Strategy - Yihui Li (Diversitas Journal, 2025)
This study explores the effectiveness of compensation systems in enhancing employee motivation and retention within auto parts enterprises in Wuhan, China, aiming to provide a basis for human resource optimization strategies. Employing a quantitative-correlational research design, the study surveyed 379 employees from diverse demographic profiles and analyzed their perceptions of compensation systems, including monetary and non-monetary components such as benefits, career development opportunities, recognition, and equity. Findings revealed that compensation systems significantly influence employee motivation and retention, with monetary compensation, career development, and recognition being key factors. Notable differences were observed in the assessment of compensation effectiveness and motivation levels based on demographic variables, such as age, income, and tenure, underscoring the importance of tailored HR strategies. The study concludes with actionable recommendations for refining compensation practices, enhancing equity, and fostering professional growth to sustain workforce satisfaction and organizational competitiveness. Future research is recommended to examine longitudinal effects and cross-industry comparisons to broaden the understanding of compensation dynamics.